PANIC HIRING HACKS FOR START- UPS: LESSON FROM A FORTUNE 500 COMPANY - G, Rajini.; Kumar, Sivasakthi (International Journal of Psychosocial Rehabilitation, 2020)
The study articulates the current difficulty in hiring faced by small-sized businesses and start-ups, emphasizing more focus on practices to attract and retain the right talents. The article also discusses the candidate’s perception to join an organization, the challenges that small-sized companies and start-ups face in attracting talent. The main reason for panic hiring among small companies is the war for talent. Fortune companies always have an edge over other companies as they hold a brand name. To resolve such situations different approaches of employer branding are brought to light and how it is developed over a period of time. Therefore the study brings out ways to resolve panic hiring. The outputs of a research study regarding hiring strategies and retention strategies of successful fortune 500 company are reported in the paper. The study emphasizes that Employer branding has a strong relationship with its Recruitment Policies and HR Practices .It is very interesting to note that the systems prevailing in an organization is important whereas individual traits have no concern with employer branding .Though a company is a start-up it should formulate clear cut policies in order to prevent panic hiring .